Program Moderasi Beragama Untuk Membentuk Insan Kamil Peserta Didik: Religious Moderation Program to Shape Perfect Human Beings Participants Educate - Bahezta Lama'a Zahra; Ali Mahmood; Sugiyar; Miftahul Ulum (Pascasarjana UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study is based on intolerant attitudes and deviant behavior among students in schools, especially junior high schools (SMP). These negative behaviors include racist slurs, marginalization of groups of different religions, and inter-ethnic slurs. Therefore, schools need to design programs that can support the cultivation of moderate character in students. This needs to be done because by implementing programs based on religious moderation, students receive direct stimulation to develop moderate attitudes, and it is hoped that students can become perfect human beings (insan kamil). This study is a qualitative field research. Data were collected through interviews, observations, and documentation, then analyzed using data analysis techniques proposed by Miles, Huberman, and Saldana, which include data collection, data condensation, data presentation, and conclusion drawing. The results of the study show that (1) Religious moderation as applied at Mitra Harapan National Trilingual Junior High School and Madiun City State Junior High School 1 is in line with nine principles, namely at-tawassuth (moderation), i'tidal (justice), tasamuh (tolerance), asy-syura (deliberation), al-islah (peace), al-qudwah (exemplary behavior), al-muwathanah (loyalty to the country), anti-violence (al-'unf), and respect for local culture (al-i'tiraf). (2) The process of instilling religious moderation education is carried out through structured, scheduled, and monitored thematic programs, including morning assemblies, stadium generals, religious activities, weekly, monthly, and annual thematic activities. (3) The impact of instilling religious moderation in students is that they gain a deeper understanding of diversity and no longer view differences in ethnicity, religion, and language as obstacles to living in harmony with one another, especially when interacting in school and community environments. Penelitian ini didasari oleh sikap intoleran dan perilaku yang menyimpang pada peserta didik di sekolah terkhusus sekolah menengah pertama (SMP). Perilaku negatif tersebut antara lain umpatan rasisme, memarjinalkan golongan yang bukan agamanya, dan umpatan antar suku. Untuk itu, sekolah perlu mendesain melalui program yang bisa menunjang penanaman karakter moderat kepada siswa. Hal ini perlu dilakukan karena dengan menerapkan program berbasis moderasi beragama, peserta didik mendapat stimulus secara langsung agar memiliki sikap moderat, dengan hal tersebut diharapkan peserta didik bisa menjadi manusia yang sempurna (insan kamil). Penelitian ini merupakan penelitian lapangan pendekatan penelitian kualitatif. Data dikumpulkan melalui wawancara, observasi dan dokumentasi kemudian dianalisis dengan menggunakan teknik analisis data yang dikemukakan oleh Miles, Huberman, dan Saldana yang meliputi pengumpulan data, kondensasi data, penyajian data, dan penarikan kesimpulan Hasil penelitian menunjukkan (1) Moderasi beragama yang diterapkan di SMP Nasional Tiga Bahasa Mitra Harapan dan SMP Negeri 1 Kota Madiun selaras dengan sembilan prinsip yaitu at-tawassuth (tengah), i’tidal (keadilan), tasamuh (toleransi), asy-syura (musyawarah), al-islah (perdamaian), al-qudwah (keteladanan), al-muwathanah (kesetiaan pada negara), anti kekerasan (al-‘unf), dan ramah budaya lokal (al-i’tiraf). (2) Proses penanaman pendidikan moderasi beragama dilaksanakan dengan program tematik yang terstruktur, terjadwal, dan terpantau, diantaranya morning assembly, stadium general, kegiatan Religius, kegiatan tematik mingguan, bulanan dan tahunan. (3) Dampak yang diperoleh dari penanaman moderasi beragama pada peserta didik yaitu, pemahaman siswa atas keberagaman semakin dalam, peserta didik tidak lagi memandang bahwa perbedaan dalam hal suku, agama, dan bahasa, menjadi halangan untuk hidup rukun antar sesama, terlebih ketika bergaul di lingkungan sekolah dan masyarakat.